Answer:
see explanation
Explanation:
(1)
y = 5x - 7x , that is
y = - 2x ( divide both sides by - 2 )
x = -
y
(2)
mx - r = y ( add r to both sides )
mx = y + r ( divide both sides by m )
x =
![(y+r)/(m)](https://img.qammunity.org/2022/formulas/mathematics/high-school/5yv01kv6bmimw1capkw2r5939jiilng7ll.png)
(3)
2x + 3y = 10 ( subtract 2x from both sides )
3y = 10 - 2x ( divide both sides by 3 )
y =
![(10-2x)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/1neb57g2jlqor88bjq5fvn8o20us6hthve.png)
(4)
5x - 3y = 4 ( subtract 5x from both sides )
- 3y = 4 - 5x ( divide both sides by - 3 )
y =
( multiply numerator/ denominator by - 1 , to 'tidy up' )
y =
![(5x-4)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/5m4l6cwvsaq48park9z6m89frg28sfhhn9.png)